DISIPLIN KERJA DAN LINGKUNGAN KERJA PENGARUHNYA TERHADAP KINERJA PEGAWAI PADA KANTOR IMIGRASI KELAS I NON TPI SERANG - Zahra, Surti; Halda, Shofa Hijria Iftinan; Pratiwi, Ika (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to know Work Discipline and Work Environment influence Employee Performance at Class 1 Immigration Offices Non TPI Serang. The data collection method used in this study was using descriptive quantitative, the population in this study were all employees of the Immigration Class I Non TPI Serang totaling 57, the sample used was 57 employees. Data collection techniques used by giving questionnaires. The analytical method used is multiple linear regression analysis processed on SPSS 26.0. The results showed that Work Discipline obtained a tcount value of 1.349 < ttable 2.004 significance value (0.183 > 0.05). The work environment obtained a tcount of 3,051 > ttable of 2,004. with a significance value (0.023 <0.05). Work Discipline and Work Environment obtained an Fcount of 18,639 > Ftable 3.17. The conclusion of this study is that work discipline and work environment affect employee performance, which means work discipline and work environment are two important factors that can affect employee performance at Class I Immigration Office Non TPI Serang